Lean Stability Approaches in Pharmaceutical Product Development, Registration, and Post-marketing CMC Change Management; Industry Survey Insights - Donnie Pulliam; Megan McMahon; Brian P. Regler; Susan Smith; Cheryl Martin; Yelizaveta Babayan; Cherokee Hoaglund-Hyzer; Michael Lesslie; Fenghe Qiu; Eric Adamec; Jin Wang; Pat Forenzo; et al. (Journal of Pharmaceutical Innovation, 2022)
Purpose This paper summarizes results from a recent pharmaceutical industry survey to understand the adoption status of science- and risk-based approaches in pharmaceutical stability (lean stability) in regulatory submissions across the full pharmaceutical product life cycle and to ascertain whether companies are deriving their stability strategies based on scientific risk or applying generic strategies. Methods A comprehensive survey was distributed to pharmaceutical companies affiliated with the International Consortium for Innovation and Quality in Pharmaceutical Development (IQ Consortium) to solicit non-proprietary responses pertaining to regulatory strategies for stability monitoring across the product life cycle, perceived risks, and health authority feedback. Results Among the 19 responding companies, utilization of lean stability approaches varied with respect to (1) phase of product life cycle, (2) specific product quality attributes cited in effective ICH guidances or which demonstrated shelf-life limiting stability trends, and (3) the degree of perceived risk of rejection by health authorities based upon companies’ degree of experience from previous regulatory submissions. Conclusion Continued collaboration between the pharmaceutical industry and health authorities—through case studies and revision/harmonization of regulatory guidances—will be essential for continued implementation of lean stability strategies to accelerate delivery of innovative medicines to the clinic and to the market.